Determining seed storage proteins of some almond (Prunus dulcis (Mill.) DA Webb.) genotypes distributed in East and Southeast of Turkey - Karatay, Huseyin; Sahin, Ahmet; Aslan, Abdullah (Mattioli 1885, 2014)
Almonds (Prunus dulcis (Mill.) D. A. Webb.) genotypes that has a large number of varieties, are grown in almost every region of Turkey except in the Eastern Black Sea region. In this study, the amount of sub-fractions (albumins, globulin A, globulin B, prolamins, and glutelins) of seed storage proteins of 32 almond genotypes were studied. Almond genotypes collected from different locations in Eastern and Southeastern Anatolian regions of Turkey. In analysis, using 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) technique. As a result the characteristic almond protein sub- fractions band profiles and the other second degree important and variable bands were revealed. These band profiles were evaluated together according to degree of similarity and variations of genotypes.
Keywords: Prunus dulcis (Mill.) D. A. Webb; seed storage proteins; SDS-PAGE; variation